Topical Issues of Information Security in Modern Economic Conditions - L. Shugunov, T.; Yu. Khashirova, T.; S. Ksenofontov, A.; A. Georgieva, M.; M. Arvanova, S. (International Journal of Engineering and Technology, 2018)
This article discusses the burning issues of ensuring information security in modern economic conditions. The purpose of this study is to analyze the current state of the effectiveness of information security in the conditions of the emerging digital economy in the Russian Federation. According to the research conducted, the number of cybercrimes in the economic sphere increases every year. The largest percentage of cybercrime is committed in the banking sector of the economy. Banks of the Russian Federation have developed information security systems and services that deal with issues of ensuring the security of economic operations. One of the key security tools is the use of cryptography. The Russian Federation is actively developing software products in the field of encryption, but these programs do not have recognition in the global information security market. The obtained results allow us to make a conclusion about the development of the market of information products in the field of protection of economic security, but it is necessary to develop software products that will meet international standards in the field of information security. The results obtained are of theoretical and practical importance for specialists in the field of security and economics. The results obtained can serve as a foundation for conducting more extensive research on the state of the information security system of the digital economy in the Russian Federation.
Keywords: Information Security; Digital Economy; Cybercrime; Cryptography; Encryption; Information Protection; Ddos Attacks; Banking Systems.